2019
DOI: 10.1039/c9ra01352k
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrasensitive fluorescent aptasensor for CRP detection based on the RNase H assisted DNA recycling signal amplification strategy

Abstract: An aptamer-based method for the ultrasensitive fluorescence detection of C-reactive protein (CRP) was developed using the ribonuclease H (RNase H) assisted DNA recycling signal amplification strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…A comparison of different immunoassay for the determination of CRP was shown in Table 1. [23][24][25][26] The results indicated that the linear range of this immunosensor was better than that of the previous reports.…”
Section: Immunosensor Response Characteristicscontrasting
confidence: 53%
“…A comparison of different immunoassay for the determination of CRP was shown in Table 1. [23][24][25][26] The results indicated that the linear range of this immunosensor was better than that of the previous reports.…”
Section: Immunosensor Response Characteristicscontrasting
confidence: 53%
“…Fluorescence spectroscopy (FS) has the advantages of simple operation, low-cost, and high selectivity. Based on the characteristics of nanomaterials (graphene oxide, 7 carbon nanotube, WS 2 , 8 molybdenum disulfide 9 ), they have been widely used in FS for the detection of biomarkers (DNA, 8 miRNA, 10 proteins, 11 small molecules 12 and exosomes 13 ). In principle, these biomarkers are adsorbed on nanomaterials through π–π stacking and hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%
“…Similar sensors have also been developed for other targets, such as C-reactive protein, tropomyosin, and Hg 2þ , with the latter being implemented in a "signal on" variation. [27,95,96] Figure 6. A) General scheme for a GO/DNA biosensor designed with an internal reference DNA.…”
Section: Sensing Based On Inhibited Adsorption Of Probe Dnamentioning
confidence: 99%
“…Similar sensors have also been developed for other targets, such as C‐reactive protein, tropomyosin, and Hg 2+ , with the latter being implemented in a “signal on” variation. [ 27,95,96 ]…”
Section: Biosensors Using Physisorbed Dna Probesmentioning
confidence: 99%